Biomimetic Hybrid Nanofiber Sheets Composed of RGD Peptide-Decorated PLGA as Cell-Adhesive Substrates - Yong Cheol Shin (Journal of Functional Biomaterials, 2015)
In biomedical applications, there is a need for tissue engineering scaffolds to promote and control cellular behaviors, including adhesion, proliferation and differentiation. In particular, the initial adhesion of cells has a great influence on those cellular behaviors. In this study, we concentrate on developing cell-adhesive substrates applicable for tissue engineering scaffolds. The hybrid nanofiber sheets were prepared by electrospinning poly(lactic-co-glycolic acid) (PLGA) and M13 phage, which was genetically modified to enhance cell adhesion thru expressing RGD peptides on their surface. The RGD peptide is a specific motif of extracellular matrix (ECM) for integrin receptors of cells. RGD peptide-decorated PLGA (RGD-PLGA) nanofiber sheets were characterized by scanning electron microscopy, immunofluorescence staining, contact angle measurement and differential scanning calorimetry. In addition, the initial adhesion and proliferation of four different types of mammalian cells were determined in order to evaluate the potential of RGD-PLGA nanofiber sheets as cell-adhesive substrates. Our results showed that the hybrid nanofiber sheets have a three-dimensional porous structure comparable to the native ECM. Furthermore, the initial adhesion and proliferation of cells were significantly enhanced on RGD-PLGA sheets. These results suggest that biomimetic RGD-PLGA nanofiber sheets can be promising cell-adhesive substrates for application as tissue engineering scaffolds.